Disparity Between Corporate and Community Land Tenure and National Land Law Accountability - RIFALDI, Ahmad Asha; PRASETYO, Yogi (Indonesia Strategic Sustainability, 2025)
The presence of corporations has had adverse effects on society, leading to conflicting perspectives regarding the legal certainty of land ownership before the enactment of Law Number 5 of 1960 concerning the Principles of Agrarian Law. It is primarily because land represents an ecological relationship, which entails both natural and legal bindings. Therefore, implementing agrarian law aims to provide legal certainty and define land ownership rights for the community. Adhering to established regulations aims to promote welfare, justice, and prosperity within the community, thereby addressing the land tenure gaps caused by corporations. This study aims to delve deeper into the gaps in land tenure and legal accountability, enhancing public understanding of agrarian law. A normative approach through a literature review was employed to conduct this research. Various sources, such as journals, websites, books, and articles about agrarian law, were consulted as references. Through this investigation, it is expected to comprehensively understand the complexities surrounding land ownership rights and legal liabilities. By shedding light on these issues, it is hoped that this research will contribute to the body of knowledge in agrarian law and facilitate the resolution of land tenure disputes caused by corporate entities. Ultimately, the aim is to achieve a harmonious balance between societal needs, corporate interests, and the principles of justice and prosperity outlined in the agrarian law.